2007
DOI: 10.1242/dev.006544
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin/TCF/Lef controls a differentiation-associated transcriptional program in renal epithelial progenitors

Abstract: In the embryonic kidney, progenitors in the metanephric mesenchyme differentiate into specialized renal epithelia in a defined sequence characterized by the formation of cellular aggregates, conversion into polarized epithelia and segmentation along a proximal-distal axis. This sequence is reiterated throughout renal development to generate nephrons. Here, we identify global transcriptional programs associated with epithelial differentiation utilizing an organ culture model of rat metanephric mesenchymal diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 50 publications
6
94
0
Order By: Relevance
“…Therefore, WTX may function in concert with WT1, possibly as a cofactor during kidney development (Rivera et al, 2009). The Wnt pathway is essential for normal kidney development and enforced expression of activated b-catenin leads to hyperproliferation of the putative metanephric mesenchyme leading to overgrowths that resemble the blastemal elements of Wilms tumor (Park et al, 2007;Schmidt-Ott et al, 2007). WT1 and WTX may both act to limit the extent of Wnt signaling as the metanephric mesenchyme condenses into mature epithelial structures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, WTX may function in concert with WT1, possibly as a cofactor during kidney development (Rivera et al, 2009). The Wnt pathway is essential for normal kidney development and enforced expression of activated b-catenin leads to hyperproliferation of the putative metanephric mesenchyme leading to overgrowths that resemble the blastemal elements of Wilms tumor (Park et al, 2007;Schmidt-Ott et al, 2007). WT1 and WTX may both act to limit the extent of Wnt signaling as the metanephric mesenchyme condenses into mature epithelial structures.…”
Section: Discussionmentioning
confidence: 99%
“…LacZ staining was carried out as described previously (Zhang et al, 2009). Whole-mount or section in situ hybridization on embryos or kidneys was carried out as described previously (Hammes et al, 2001;Schmidt-Ott et al, 2007). Riboprobes for E-cadherin and Cldn4 were produced from PCR fragments (see Table S1 in the supplementary material).…”
Section: Immunofluorescence Staining Lacz Staining and In Situ Hybrimentioning
confidence: 99%
“…Conversely, Ecadherin transcription is re-induced in mesenchymal cells that undergo epithelial conversion during kidney development. Remarkably, in this context, the induction of E-cadherin is temporally coordinated with the expression of multiple additional components of the apical junctional complex, suggesting that a common molecular mechanism orchestrates the induction of apical junctional complex components during epithelial differentiation (Schedl, 2007;Schmidt-Ott et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…25 Elegant studies have shown that WNT/b-catenin signaling is a necessary and sufficient trigger of the early stages of nephron differentiation. 26,27 We linked the human WNT4 variant to defective WNT signaling by two independent model systems. In the first model, utilizing HEK293, WNT4 by itself does not trigger WNT/b-catenin signaling but rather inhibits a Wnt3A-induced signal, whereas the WNT4 variant induces significantly exaggerated inhibition.…”
Section: T G G a A G T C A T G G A C T C G Gmentioning
confidence: 99%